2010
DOI: 10.1055/s-0030-1263321
|View full text |Cite
|
Sign up to set email alerts
|

Unterschiede im Verschreibungsverhalten von Antibiotika bei Allgemein- und Kinderärzten in Hessen

Abstract: In this retrospective analysis, pediatricians were associated with a lower antibiotic prescription rate regarding diagnoses where antibiotic therapy is not clearly indicated. However, in diagnoses where antibiotic therapy is clearly indicated, no differences in prescription rates between pediatricians and GPs were observed. Further studies are warranted to gain insight into different treatment strategies between different groups of medical practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
0
4
0
3
Order By: Relevance
“…Of these, 25 studies did not fulfil the eligibility criteria, for the following reasons: no data on children ( n = 7 studies), other country than in this study ( n = 12), no data on diagnoses of this study ( n = 4), no data on antibiotic prescription rates ( n = 2). Eleven studies [ 2 , 7 , 8 , 75 82 ] with a total of 16 diagnosis groups (cough/tracheitis/bronchitis: n = 2, sore throat/pharyngitis: n = 2, ear pain/otitis: n = 6, Upper RTI/RTI: n = 6) were eligible for comparisons (further data in Table 5 ). All 16 comparison groups had higher antibiotic prescription rates than the corresponding C-, and A-groups of this study ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 25 studies did not fulfil the eligibility criteria, for the following reasons: no data on children ( n = 7 studies), other country than in this study ( n = 12), no data on diagnoses of this study ( n = 4), no data on antibiotic prescription rates ( n = 2). Eleven studies [ 2 , 7 , 8 , 75 82 ] with a total of 16 diagnosis groups (cough/tracheitis/bronchitis: n = 2, sore throat/pharyngitis: n = 2, ear pain/otitis: n = 6, Upper RTI/RTI: n = 6) were eligible for comparisons (further data in Table 5 ). All 16 comparison groups had higher antibiotic prescription rates than the corresponding C-, and A-groups of this study ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotic prescription rates ranged from 31.0% (nonspecific RTI [ 7 ]) to 84.1% (OM [ 77 ]). Compared to the rates in the A-groups, prescription rates in the comparison groups were 6.7 [ 80 ] to 13.3 [ 77 ] times higher for cough/bronchitis, 26.2 [ 77 ] to 29.2 [ 81 ] times higher for sore throat/pharyngitis, 6.1 [ 75 ] to 12.2 [ 77 , 79 ] times higher for ear pain/OM, and 6.9 [ 7 ] to 15.1 [ 78 ] times higher for upper RTI/RTI.…”
Section: Resultsmentioning
confidence: 99%
“…Gender differences concerning antibiotic use are already known: Data from the National Ambulatory Medical Care Survey from 1992 in the USA indicate a significant positive association between antibiotic consumption and female sex [29]. Moreover, findings from Abbas et al suggest higher antibiotic use for girls compared to boys in all age groups except for 2-4-years old children [30]. Our results regarding regional differences are in line with the results of the EVA survey ( E inflüsse auf die ärztliche V erschreibung von A ntibiotika in Deutschland) which investigates influences on prescribing patterns by physicians in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study found that pressure exerted to obtain antibiotics is often overestimated [16]. This is confirmed by other studies, which showed that the interpretation of patient expectations is difficult and leaves room for uncertainty [17,18]. A Cochrane Review examined 10 studies on shared decision making (SDM) in antibiotic prescriptions for acute respiratory infections and found that it reduced the prescription of antibiotics by 40 % [19].…”
Section: Introductionmentioning
confidence: 70%